Effect of thinning of flowers on fruit set in the cultivar 'Algérie' in the Marina Baixa - Soler E.; Juan N. (First international symposium on loquat, 2003)
In order to obtain optimum and profitable commercial fruit size in loquat culture thinning of flowers and-or fruits is required. In the Marina Baixa area, thinning is applied at different timings. However, in our climatic conditions with the cultivar 'Algerie' a range of successful results on fruit set is obtained depending on the phenological growth stage at when thinning is applied. Results from this study showed that flower thinning made in the first stages of growth resulted in increased fruit set. It seems that flowers are an important sink for nutrients and a substantial competition for fruit growth. This fact implies that the best time for flower thinning depends on the climate. In those areas with poor setting, thinning in the first stages of development can improve fruit setting. However, in those areas with heavy fruit set, thinning of flowers should be delayed to minimize fruit set and to decrease the need of fruit thinning.
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)